2006
DOI: 10.1021/cg0504612
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Intercalated Ni/Al Hydrotalcites Prepared by the Partial Decomposition of Urea

Abstract: Layered double hydroxides containing Ni 2+ and Al 3+ have been synthesized by homogeneous precipitation through urea hydrolysis. The nature of the interlayer species changes according to the treatment of the samples, formation of interlayer (NH 2 )COOspecies being observed immediately after precipitation, which undergo transformation to carbonate after hydrothermal treatment. Simultaneously, liberation of ammonia during decomposition under hydrothermal conditions gives rise to formation of [Ni(NH 3 ) 6 ] 2+ sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
37
0
2

Year Published

2007
2007
2012
2012

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(42 citation statements)
references
References 21 publications
3
37
0
2
Order By: Relevance
“…Recently, Kloprogge et al [12] suggested that LDHs synthesized via the urea method intercalate (NH 2 )COO − anions, an interlamellar species that, according to the authors, would account for the apparent C 2v character of the bands assigned to CO 2− 3 . The absence of bands due to NH vibrations (2960-2850 cm −1 ) in Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Recently, Kloprogge et al [12] suggested that LDHs synthesized via the urea method intercalate (NH 2 )COO − anions, an interlamellar species that, according to the authors, would account for the apparent C 2v character of the bands assigned to CO 2− 3 . The absence of bands due to NH vibrations (2960-2850 cm −1 ) in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The subsequent evolution of the coprecipitated hydroxides to form the final solid depends strongly on the reactivity of the involved metal ions; e.g., for labile ions, such as Cu 2+ and Zn 2+ , double basic carbonates form readily [38]. Thus, owing to the higher lability of Al 3+ than of Cr 3+ (Table 2), less stringent aging conditions are required for the preparation of Al(III)-containing LDHs via the urea method [9][10][11][12]. It should be recognized here that homogeneous nucleation of Zn(II)-Cr(III) LDHs takes place under the conditions provided by slow pH-titration experiments [40].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example MgMn 2+ Mn 3+ -LDH was synthesized through oxidation of Mn 2+ to Mn 3+ in the solid state [19] and Co 3+ containing LDHs, MgCo II Co IIIand Co II Co III -LDHs was also studied [20][21][22][23]. Several synthetic methods have been used to synthesize hydrotalcites and spinel powder that include the precipitation [24][25][26], hydrothermal [27], salt oxide method [28], urea reduction [29,30], electrochemical [31,32], mechanical activation with subsequent annealing [33], and sol-gel [34]. Co-precipitation is a simple and effective method for the preparation of multi-component oxides [35].…”
Section: Introductionmentioning
confidence: 99%
“…However, this concept could be acceptable if the pure iron (oxy) hydroxide is present. Although the pH IEP of goethite and CaCO 3 have been generally known to be 8.5 * 9.6 and 7 * 11, respectively (Erdemoglu et al 2004;Kloproeeg et al 2006;Dzombak and Morel 1990), the results of zeta potential measurement showed that the pH IEP values of CMDS were 5 and 4.5 with the suspension of DI and 0.01 M NaCl, respectively (see Fig. 4).…”
Section: Isoelectric Point Of Ph (Ph Iep ) Of Cmdsmentioning
confidence: 93%